Characterisation of the mixing of non‐newtonian fluids with a scaba 6SRGT impeller through ert and CFD. (22nd December 2011) - Pakzad, Leila; Ein‐Mozaffari, Farhad; Upreti, Simant R.; Lohi, Ali
Abstract An attempt has been made to study the mixing of yield‐pseudoplastic fluids with a Scaba 6SRGT impeller using electrical resistance tomography (ERT) and computational fluid dynamics (CFD). The ERT system with four sensor planes, each containing 16 equispaced stainless steel electrodes, was used to measure the mixing time. The multiple reference frames (MRF) technique and the modified Herschel–Bulkley model were applied to simulate the impeller rotation and the rheological behaviour of the non‐Newtonian fluids, respectively. To validate the model, the CFD results for the power consumption were compared to the experimental data. The validated model was then employed to obtain further information regarding the averaged impeller shear rate, impeller circulation, and pumping capacities. The CFD and ERT data were utilised to investigate the effect of the impeller power, fluid rheology, and impeller size on the mixing time. The mixing time results obtained in this study were in good agreement with those reported in the literature. © 2011 Canadian Society for Chemical Engineering